(untitled) (Investigación + Acción, 2021)
With the exponential increase in the population on Earth, there is a concern for the sustainability of architecture as an item that consumes a great deal of non-renewable energy. Today, caused by the SARS-CoV-2 pandemic, it is compounded by imperative needs for comfort and health. Bioclimatic architecture uses and optimizes natural resources to improve living conditions, reduce energy costs and reduce environmental impact. The objective of this work is to analyze the bioclimatic conditions in the Mar del Plata region to facilitate decision-making for the design of buildings. The methodology consists of the study of several central themes: climate, comfort, shape, sunlight and wind, based on data from the National Meteorological Service. Simultaneously, the IRAM 11603 standard and the reference bibliography are taken into account. The results obtained indicate that the constructions in the region should respond to a predominantly cold and humid climate. The architecture would have to maintain a certain compactness, use thermal insulation, have good orientation to take advantage of the sun in the cold months, provide good ventilation and protect itself from the winds.